If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = -7x + -96 Reorder the terms: 5x = -96 + -7x Solving 5x = -96 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 5x + 7x = -96 + -7x + 7x Combine like terms: 5x + 7x = 12x 12x = -96 + -7x + 7x Combine like terms: -7x + 7x = 0 12x = -96 + 0 12x = -96 Divide each side by '12'. x = -8 Simplifying x = -8
| 15=20-x | | 5x+8=6x+10 | | 5x*8=6x+10 | | .2m=.3(m+5) | | 8a-13=12+5a-7 | | x^2/4-5+x=-5 | | 23h=207 | | 6*42+7y=42 | | 5x5+2/2 | | g(x)=-log(x)+2 | | 6x+7*42=42 | | 5x=450 | | -322=14x | | 9y+2=13y+11 | | -7x^2+8x+10+2x^2+6x+[-5]= | | h=-16t^2+h | | 4x^2-7x+9=-19x | | 9x+6x-12x=-7x-2x-12+5x | | (2x-4)/(x-5)=0 | | y=0.5+5.33 | | 2x-4/x-5=0 | | 4y+9=13y+11 | | 90-7.68x=66.96 | | 3x+y=5y+20 | | 3x=4y+20 | | 3x=4y+20 | | 4(y-2)+3(2y-1)=6(2y-3) | | 90=x-5 | | 3m+y=4m-7 | | 4-2x/3=-1/6+x | | -4x+3/2x=7/2x | | 1/2(8w-6)=17 |